2001
DOI: 10.1046/j.1432-1327.2001.01990.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of ADAMTS‐5 in synovium

Abstract: ADAMTS proteinases, belonging to the adamalysin subfamily of metalloproteinases, have been implicated in a variety of cellular events such as morphogenesis, cell migration, angiogenesis, ovulation and extracellular matrix breakdown. Aggrecanase-1 (ADAMTS-4) and aggrecanase-2 (ADAMTS-5) have been identified in cartilage and are largely responsible for cartilage aggrecan breakdown. We have shown previously that synovium, the membrane lining diarthrodial joints, generates soluble aggrecanase activity. We report h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 47 publications
6
81
0
1
Order By: Relevance
“…3) showed that they resulted from typical aggrecanase cleavages in poorly glycosylated regions of the aggrecan core protein. These cleavage sites have been reported for both ADAMTS-4 and -5 [17,31,42]. We describe here for the first time the N-terminal sequences of the major aggrecan fragments generated by ADAMTS-1.…”
Section: Aggrecanolytic Activity Of Rhadamts Enzymessupporting
confidence: 63%
See 3 more Smart Citations
“…3) showed that they resulted from typical aggrecanase cleavages in poorly glycosylated regions of the aggrecan core protein. These cleavage sites have been reported for both ADAMTS-4 and -5 [17,31,42]. We describe here for the first time the N-terminal sequences of the major aggrecan fragments generated by ADAMTS-1.…”
Section: Aggrecanolytic Activity Of Rhadamts Enzymessupporting
confidence: 63%
“…ADAMTS-5 purified from cartilage-conditioned medium has revealed multiple bands in the range of 40-65 kDa [17]. In addition, similarly processed forms of the enzyme have been detected in synovium-conditioned medium from arthritis patients [31] and in a GnHCl extract from cartilage of an arthritic patient [23].…”
Section: Purification and Characterization Of Rhadamts Enzymesmentioning
confidence: 94%
See 2 more Smart Citations
“…In rheumatoid arthritis synovitis is associated with hyperplasia of the synoviocytes, an infiltration of mononuclear cells including B cells, T cells and macrophages into the synovial sublining, and the formation of a locally invasive pannus (Lee & Weinblatt, 2001). A number of studies have shown that in arthritic pathologies the synovial expression of a number of proteases, including MMP collagenases, ADAMTS aggrecanases and MMP-3, is increased as are the levels of these proteases in the synovial fluid (Hulejová et al, 2007;Smeets et al, 2003;Tchetverikov et al, 2004;Vankemmelbeke et al, 2001;Vankemmelbeke, Ilic, Handley, Knight, & Buttle, 1999). In vitro studies have implicated synovium-derived factors, in particular proinflammatory cytokines (Fell & Jubb, 1977;Saklatvala, Pilsworth, Sarsfield, Gavrilovic, & Heath, 1984) and proteases (Vankemmelbeke et al, 1999(Vankemmelbeke et al, , 2001) as mediators of cartilage destruction.…”
Section: Synovium: Inflammation Hyperplasia Pannus Formation and Prmentioning
confidence: 99%